A theoretical model of commercialisation. (28th August 2007) - Poole, Graham R.; Moore, Roger
Commercialisation of intellectual property is an important means by which academic science contributes to economic growth. It has attracted considerable interest, but a systematic treatment largely remains lacking. This paper attempts to fill the gap by setting forth a theoretical model that examines the conditions that must hold for commercialisation to occur. It also analyses four main barriers to the process. The model illustrates why the development gap exists and explains why weak economies often fail to capitalise on a strong science base. It further highlights the potential role to be played by third parties in encouraging the process.